Knowledge and attitudes toward epilepsy among primary, secondary and tertiary level teachers - Fábio Galvão Dantas; Gibran Agra Cariri; Gustavo Agra Cariri; Antônio Roberto Vaz Ribeiro Filho (Arquivos de Neuro-Psiquiatria)
The attitudes toward people with epilepsy are influenced by the degree of knowledge of the condition. Teachers usually do not receive any formal instruction on epilepsy during their training. This study was done to access three hundred teachers' knowledge and attitudes toward epilepsy by answering a questionnaire in order to quantify their knowledge, attitude and practice toward epilepsy. Almost all the teachers had heard about epilepsy yet could not demonstrate discrimination among the students. Some teachers still thought that epilepsy was contagious. A few others either objected to having epileptic children in their classes or did not think that an epileptic child could achieve higher studies. The knowledge about the clinical characteristics and initial procedures to attend a person during a seizure was unsatisfactory. We conclude that schools should offer some kind of knowledge or assistance in health services and physicians must ensure that these teachers have sufficient knowledge of epilepsy. Also general public education campaigns should be encouraged in this field.